(untitled) (Bangladesh Rice Journal, 2015)
Eight districts represent Chittagong and Rangamati agricultural regions having 30637 sq km areas. These regions face natural calamities like Sidr, Aila, Resmi, salinity and soil erosion. Crops are grown in 852436 ha of land. Single crop is grown in 58.48% areas in Chittagong Hill Tracts (CHT) region, while in Chittagong agriculture region two crops are grown in about 51% areas. Rice production or its expansion is hindered because of factors like excessive or no rainfall in pre-monsoon season, soil and water salinity, water stagnation in wet season, lack of suitable rice varieties and fresh water in dry season, good income source other than farming, soil erosion, absentee farmers etc. Growing of salt tolerant varieties, organic amendments, use of cover crop, improved irrigation system can be adopted among others for land productivity improvement in coastal areas. Sorjan or ditch and pyramid or ridge systems can be utilized in coastal tidal areas. Installing subsurface drainage system and floating beds could be used in water stagnant conditions. Zero or minimum tillage following dibbling/pegging method, rain water harvesting, improved Jhum, community based seepage water harvesting, homestead gardening and floriculture are the adaptation options in hill agriculture. Bangladesh Rice j. 2014, 18(1&2): 54-64